Penyelesaian Sengketa Penjualan Tanah Sebagai Harta Waris Tanpa Persetujuan Pihak Waris Lain - Maksufah, Eva Wardatul (UM Purwokerto Press, 2024)
It is very common that inherited land is sold without the consent of all heirs. The rights of other heirs are threatened by this action. This abstract discusses how to resolve problems that arise as a result of such actions. The injured heirs have the right to file a lawsuit in accordance with the Civil Code (KUHPer). This type of lawsuit can be in the form of compensation for losses or cancellation of the land sale and purchase. Mediation is another way to resolve the problem. The purpose of mediation is to reach an agreement between the land buyer and the injured heirs. It is hoped that this abstract provides an overview of efforts to resolve inheritance land disputes that do not have the consent of all heirs.